2013
DOI: 10.1016/j.ibmb.2012.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and functional characterization of inward-rectifying potassium (Kir) channels from Malpighian tubules of the mosquito Aedes aegypti

Abstract: Inward-rectifying K+ (Kir) channels play critical physiological roles in a variety of vertebrate cells/tissues, including the regulation of membrane potential in nerve and muscle, and the transepithelial transport of ions in osmoregulatory epithelia, such as kidneys and gills. It remains to be determined whether Kir channels play similar physiological roles in insects. In the present study, we sought to 1) clone the cDNAs of Kir channel subunits expressed in the renal (Malpighian) tubules of the mosquito Aedes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
84
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(97 citation statements)
references
References 76 publications
(129 reference statements)
13
84
0
Order By: Relevance
“…As shown in Figure 3, blood-feeding elicits a sustained down-regulation of two transcripts encoding Kir channel subunits (AAEL008931-RA, AAEL013373-RA) and one transcript encoding a putative NKCC (AAEL006180-RA). We recently cloned and characterized AAEL008931-RA (Kir2B) from the Malpighian tubules of A. aegypti and have confirmed that it encodes a barium-sensitive Kir channel [41]. The NKCC is an ortholog of Drosophila melanogaster Ncc69, which has been shown to a play a key role in fluid and K + secretion in fruit fly Malpighian tubules [42].…”
Section: Resultsmentioning
confidence: 93%
“…As shown in Figure 3, blood-feeding elicits a sustained down-regulation of two transcripts encoding Kir channel subunits (AAEL008931-RA, AAEL013373-RA) and one transcript encoding a putative NKCC (AAEL006180-RA). We recently cloned and characterized AAEL008931-RA (Kir2B) from the Malpighian tubules of A. aegypti and have confirmed that it encodes a barium-sensitive Kir channel [41]. The NKCC is an ortholog of Drosophila melanogaster Ncc69, which has been shown to a play a key role in fluid and K + secretion in fruit fly Malpighian tubules [42].…”
Section: Resultsmentioning
confidence: 93%
“…Interestingly, no functional channel activity was observed with attempts at expression of Irk3 in Xenopus oocytes or Drosophila S2 cultured cells, whereas both Irk1 and Irk2 possessed inwardly rectifying K ϩ channel activity (7). Similarly, no channel activity was observed in Xenopus oocytes expressing the Aedes aegypti Irk3 homolog, AeKir3, although it is highly expressed in the mosquito tubule (29). In addition, recent immunolocalization data indicates that AeKir3 is expressed in intracellular punctae in the mosquito tubule (28).…”
Section: Inwardly Rectifying Kmentioning
confidence: 99%
“…Examples include the yellow fever mosquito Aedes aegypti (22,41), the forest ant Formica polyctena (17), the Chagas vector Rhodnius prolixus (12), the agricultural pest Locusta migratoria (14), and the mealworm Tenebrio molitor (45). In addition, transcripts for inwardly rectifying K ϩ channels are expressed in the Malpighian tubules of Aedes aegypti, the vector for yellow fever, dengue, and chikungunya (29); Anopheles gambiae, the malaria vector (30); and the bed bug Cimex lectularius (21). Drugs targeting renal tubule inwardly rectifying K ϩ channels are currently being developed as mosquitocidal insecticides in Aedes aegypti (31,32,38).…”
Section: Inwardly Rectifying Kmentioning
confidence: 99%
See 1 more Smart Citation
“…We hypothesized that the Kir subunit immunoreactivity would be expressed primarily on the basolateral membrane of principal cells given the results of our previous physiological studies on mosquito Malpighian tubules (Beyenbach and Masia, 2002;Masia et al, 2000;Piermarini et al, 2013;Scott et al, 2004). Moreover, a previous in situ hybridization study in Malpighian tubules of Drosophila melanogaster by the Dow laboratory found the expression of Kir subunit mRNAs to occur only in principal cells (Evans et al, 2005).…”
Section: Introductionmentioning
confidence: 94%